“Mind over mud”: governing health and space in colonial Hong Kong and Shanghai - Stephenson, Freddie (2020)
This thesis comparatively assesses the nature of health, space, and culture in colonial Hong Kong and Shanghai’s International Settlement in the late nineteenth and early twentieth century. It examines how the two distinct forms of British imperialism manifested in these two possessions fundamentally shaped the concepts of health that evolved locally, and the practices designed to manage that broad concept. In so doing, this thesis also seeks to reflect the lived reality of health in the contemporary imperial context, positioning it as heuristically produced in collaboration between imperial rulers and imperial citizens. In this process, it elaborates how the cultural associations of spaces intimately impacted how people conceived of the healthiness of those spaces, and in turn how space was managed as a result. Through this cultural comparative lens, this thesis elaborates the underlying subjectivities between different forms of imperialism with a British complexion. It shows how old colonial tropes of racialised bodies and their environments gained firm ground in both cities, but most of all this thesis iterates on recent historical works showing the centrality of visions of domesticity on both sides of the colonial equation. Together this thesis seeks to intertwine the complex nature of health as a societal construct with historiographical calls for greater insights across different imperial systems and for the incorporation of colonialism into the history of modern China.